Experimental investigation on H-section buckling-restrained braces with partially restrained flange. (15th November 2019) - Wang, Chun-Lin; Gao, Yuan; Cheng, Xiaoqiang; Zeng, Bin; Zhao, Senlin
Highlights: A new H-section BRB with partially restrained flange is proposed. BRB shows stable hysteretic performance and high energy absorption capacity. Large out-of-plane deformation of the unrestrained flange is detected. Web of H-section core is effectively restrained by top and bottom flanges. Abstract: For the development of buckling-restrained braces (BRBs) with high bearing capacity and light weight, a new type of all-steel buckling-restrained braces with H-section steel core (HBRBs) is proposed. The restraining member of the new HBRB mainly consists of the restraining plates and the steel channels. The outside of flange of the H-section steel core is restrained by the restraining plate, the edge parts of the inside of flange are restrained by the steel channel, and web of the H-section steel core is unrestrained. There is adequate operation space for welding stiffeners in the elastic segment of the H-section steel core, and the cross-section of the restraining member is uniform along the longitudinal direction. Thus, the processing complexity of the new HBRB is reduced. First, cyclic tests are performed on the new HBRBs and one conventional HBRB of which the inside of flange is unrestrained. Then, numerical simulations are carried out to further investigate the hysteretic performance and deformation mode of the new HBRB. Test and numerical simulations demonstrate that the new HBRB shows stable hysteretic performance, and the energy absorption capacity of the HBRB can be significantly improved when the inside of flange is partially restrained. Decreasing the restrained width of the inside of flange is capable of reducing the normal contact force between the H-section steel core and the restraining member, also reducing the compression strength adjustment factor of the new HBRB. There is no visible decrease in the compressive strength of web with the strain amplitude, demonstrating that web can be effectively restrained by the top and bottom flanges.